Cardiovascular risk factors and proteinuria in Toba aborigines from Chaco, Argentina - Bianchi, María Eugenia Victoria (2013)
Fil: Bianchi, María Eugenia Victoria. Universidad Nacional del Nordeste. Facultad de Medicina; Argentina.